Writing Skills Development: A Balancing Perspective of Brain Function in Elementary Schools - Ririen Wardiani; Indrya Mulyaningsih; Siriporn Maneechukate (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractWriting is a skill that involves creativity. It can be triggered by using a stimulating activity of both hemispheres of the brain. This study aims to describe the improvement of narrative writing skills by using a learning model based on the balancing of the functions of the right and left hemispheres of the brain. The research method used is classroom action research through three implementation cycles from January – December 2019 in three elementary schools in Ponorogo, Indonesia. The sample of this study was 72 students of grade 4. The data collected through using tests, observations, and interviews were then analyzed both qualitatively and quantitatively. The results showed that to produce good writing, students need to be guided and given a lighter. After balancing the functions of the cerebral hemispheres, 86% or 62 students met the minimum completeness score. The students' ability in writing narratives has increased significantly, especially in the aspects of content, content organization, vocabulary, grammar, and spelling.Keywords: narrative writing; the balancing of the functions of the cerebral hemispheres; the brain learning model.AbstrakMenulis merupakan keterampilan yang melibatkan kreativitas. Ini dapat dipicu dengan menggunakan aktivitas stimulasi kedua belahan otak. Penelitian ini bertujuan untuk mendeskripsikan peningkatan keterampilan menulis narasi dengan menggunakan model pembelajaran berbasis keseimbangan fungsi belahan otak kanan dan kiri. Metode penelitian yang digunakan adalah penelitian tindakan kelas melalui tiga siklus pelaksanaan dari Januari – Desember 2019 di tiga sekolah dasar di Ponorogo, Indonesia. Sampel penelitian ini adalah 72 siswa kelas 4. Data yang dikumpulkan melalui tes, observasi, dan wawancara kemudian dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa untuk menghasilkan tulisan yang baik, siswa perlu dibimbing dan diberi pemantik. Setelah dilakukan penyeimbangan fungsi belahan otak, 86% atau 62 siswa memenuhi nilai ketuntasan minimal. Kemampuan siswa dalam menulis narasi meningkat secara signifikan, terutama dalam aspek isi, organisasi isi, kosa kata, tata bahasa, dan ejaanKata kunci: menulis narasi; menyeimbangkan fungsi belahan otak; model pembelajaran otak.